Comparative Docking of Laccase Enzyme Isoforms on Quinolone Pollutants - Nur'aini Nur'aini; Hanzhola Gusman Riyanto (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2026)
A molecular study employed molecular docking simulations to investigate potential interactions between the laccase enzyme and the quinolone compound. Quinolones, a class of synthetic antimicrobial agents that are also environmental pollutants, were tested for their interactions with the laccase enzyme, known for degrading various organic compounds. This study investigated the binding affinity and stability of the laccase-quinolone complex, with and without water, using both rigid and flexible docking methods. The docking result suggests feasible recognition/binding of quinolones by the laccase active site regions, with binding energies ranging from −6.879 to −8.633 kcal·mol−1 in the absence of water and from −5.543 to −6.547 kcal·mol−1 in the presence of water. The RMSD values for the laccase-quinolone complex varied between 0.7519 and 1.655, indicating a stable interaction, particularly with nalidixic acid as the ligand. A comparison study was conducted with other laccase enzymes, implying valuable insight into the potential use of T. hirsuta laccase for quinolone degradation, offering a promising biotechnological approach for environmental applications. The MD simulations also demonstrated similar results, which enzyme-quinolone complex had a comparatively low RMSF, indicating that the laccase enzyme facilitated the degradation of the quinolone.